Efficacy of biocontrollers and fungicides for the control of Pythium sp. in chrysanthemum (Dendranthema grandiflora (Ramat.) Kitam.) - Merchán-Gaitán, Julia Bibiana; Aragón-Caballero, Liliana María; Álvarez-Herrera, Javier Giovanni (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Damping off  is caused by Pythium sp. in seedlings, which is the main cause of losses in chrysanthemum crops. This research aimed to evaluate the optimal dose of biocontrollers and chemical fungicides for Pythium sp. The application of the treatments was carried out both in a laboratory and on a greenhouse crop. A completely randomized design was used with 10 treatments (control, metalaxyl and chlorothalonil, azoxystrobin, Trichoderma harzianum, and Bacillus subtilis), applied at two doses: 100% and 150% of the commercial application. The results obtained in the laboratory phase showed that the inoculated control had the highest mycelial growth of Pythium sp., 36.43 cm in diameter. The treatments with chemical fungicides presented 100% control since there was no growth of Pythium sp. In the greenhouse, the chrysanthemum cultivation had the best results when T. harzianum was applied at a dose of 150% since only 9.33% incidence was observed. In terms of severity, the most effective treatment was the commercial dose of T. harzianum, with 4.9%. The best performance of the agronomic characteristics in the chrysanthemum plants was seen with the application of T. harzianum at a dose of 150% because the plants presented  higher plant height, fresh radicular mass, dry root mass, fresh aerial mass, mass dry air, number of buttons, floral diameter and floral mass.